Microfluidic Lateral Flow Cytochrome P450 Assay on a Novel Printed Functionalized Calcium Carbonate‐Based Platform for Rapid Screening of Human Xenobiotic Metabolism. (14th June 2018) - Jutila, Eveliina; Koivunen, Risto; Kiiski, Iiro; Bollström, Roger; Sikanen, Tiina; Gane, Patrick
Abstract: Cytochrome P450 (CYP) is a superfamily of enzymes in charge of elimination of the majority of clinically used drugs and other xenobiotics. This study focuses on the development of a rapid microfluidic lateral flow assay to study human phase I metabolism reactions mediated by CYP2A6 isoenzyme, the major detoxification route for many known carcinogens and drugs, with coumarin 7‐hydroxylation, as the prototype model reaction. Assay fabrication utilizes custom‐designed porous functionalized calcium carbonate (FCC) coatings and inkjet‐printed fluid barriers. All materials used are novel and carefully chosen to preserve biocompatibility. The design comprises separate zones for reaction, separation and detection, and an absorbent pad to keep the assay wet for extended periods (up to 10 min) even when heated to physiological temperature. The concept enables CYP assays to be made at lower cost than conventional well‐plate assays, while providing increased selectivity at equally high speed, owing to the possibility for simultaneous chromatographic separation of the reaction products from the reactants on the FCC coating. The developed concept provides a viable rapid prediction of the interaction risks related to metabolic clearance of drugs and other xenobiotics, and exemplifies a novel coating technology illustrating the opportunity to broaden application functionality. Abstract : Human phase I metabolism interactions mediated by cytochrome P450 (CYP) can be studied using a microfluidic lateral flow assay constructed from functionalized calcium carbonate (FCC) and microfibrillated cellulose. The FCC‐based platform coupled with fluorescence detection offers a viable method for studying CYP enzyme interactions in vitro, at comparatively low cost, but with significantly increased selectivity compared to conventional well‐plate assays.